Molecular characterisation of alpha-thalassaemia in patients investigated for hypochromic microcytic indices in Hospital Universiti Sains Malaysia - Vijian, Divashini (2023)
Alpha (α)-thalassaemia is a common genetic disorder that affects 5 % of the worldwide population. Deletional or non-deletional mutations of one or both HBA1 and HBA2 on chromosome 16 cause a reduction/abnormal in the production of α globin chains, a component of haemoglobin (Hb) which are required for the formation of red blood cells (RBC). Thus, reduced Hb leads to anaemia. Many genetic mutations in α- thalassaemia have been discovered, which produced wide spectrum of clinical manifestation, ranging from asymptomatic to lethal. This study focused on the characterisation of RBC parameters and molecular based on α-thalassaemia mutations to determine the prevalence and to describe the RBC parameters based on the mutations detected. A cross-sectional study involving 136 suspected α-thalassaemia patients was collected. The DNA extracted from blood samples was subjected to the multiplex GAP-polymerase chain reaction, multiplex amplification refractory mutation system polymerase chain reaction (MARMS-PCR), and duplex-polymerase chain reaction to detect common deletional and non-deletional α mutations, respectively. Multiplex ligation dependent probe amplification and Sanger sequencing were performed to detect rare mutations in patients that do not carry any common mutations. The prevalence of α-thalassaemia in this study was 47.1 %. Thirty-nine and 1.4 percent of patients were found to have heterozygous and homozygous α- thalassaemia mutations, respectively, with 6.6 percent being compound heterozygous. Among the patients, the following genotypes were found: -α3.7/αα (15.4 %), -α4.2/αα (3.7 %), --SEA/αα (7.4 %), αCSα/αα (10.3 %), αAdanaα/αα (0.7 %), αQuong Szeα/αα (1.5 %), -α3.7/-α3.7 (0.7 %), αCSα/αCSα (0.7 %), -α4.2/αCSα (0.7 %), –SEA/αCSα (1.5 %), –SEA/αQuong Szeα (0.7 %), -α3.7/αAdanaα (0.7 %), --SEA/-α3.7 (2.2 %) and αCSα/αAdanaα (0.7 %). Statistical analysis of RBC parameters according to the mutations was performed. A few indicators, such as Hb (p=0.020), mean corpuscular volume (p=0.008), mean corpuscular haemoglobin (p=0.018), RBC (p=0.029) and haematocrit (p=0.049), showed significant changes among patients with deletional mutations, but there were no significant differences between patients with non-deletional mutations. patients with single gene deletional and non-deletional mutations shows only significant differences for HbA2 (p=0.028). A wide range of RBC parameters were observed among the patients, including those with the same genotypes. Thus, based on RBC parameters alone, they are not sufficient to describe the specific mutations of α- thalassaemia.